0=-300 + 200/(1-x) - 100/(1-x)
add 3oo both sides
300 = 200/(1-x) -100/(1/x)
300= 100/(1-x)
multiply both sides by (1-x)
300(1-x)= 100
300-300x=100
divide by 100 both sides
3-3x=1
-3x=1-3
-3x=-2
3x=2
x=2/3
2006-12-07 05:56:28
·
answer #1
·
answered by snowgoose8 2
·
0⤊
1⤋
This looks just like the other question you asked.
Start by getting a common denominator of (1-x) for each fraction. In other words, multiply the -300 by (1-x)/(1-x)
This gives you
-300 (1-x) ... 200 ... 100
------------- + ------ - ------- = 0
..... (1-x) ......(1-x) . (1-x)
Now combine the numerators:
-300 (1 - x) + 200 - 100
------------------------------- = 0
................ (1 - x)
Now multiply by (1 - x), not this will make the denominator disappear. By definition, x can't equal 1 or else your original equation would be wrong, so we don't have a problem doing this:
-300(1 - x) + 200 - 100 = 0
-300 + 300x + 100 = 0
-200 + 300x = 0
300x = 200
x = 2/3
As a double check:
-300 + 200 / (1 - (2/3)) - 100 / (1 - (2/3)) = ?
-300 + 200 / (1/3) - 100 / (1/3) = ?
-300 + 200 * 3 - 100 * 3 = ?
-300 + 600 - 300 = 0 <-- check
So the answer is x = 2/3
2006-12-07 14:02:10
·
answer #2
·
answered by Puzzling 7
·
0⤊
0⤋
First
200(1-x) - 100/(1-x) can be simplified to 100/(1-x)
Therefore,
0 = -300 +100(1-x)
Then add 300 to both side get
300 = 100(1-x)
Then multiply each side by (1-x) gets
300 (1-x) = 100
300 - 300x = 100
200 = 300x
x = 2/3
2006-12-07 14:00:51
·
answer #3
·
answered by MustangGT 2
·
0⤊
0⤋
Simplify right side to 100/(1-x) -300
The equation is equivalent to
100/(1-x) -300 = 0
Divide out 100
1/(1-x) -3 = 0
multiply both sides by 1-x
1 - 3(1-x) = 0
1-3 + 3x = 0
3x -2 = 0
3x = 2
x = 2/3
2006-12-07 13:59:00
·
answer #4
·
answered by MathMaven53 1
·
0⤊
0⤋
X = 0.6 recurring. The sum of 200/(1-x) - 100/(1-x) has to be equal to 300 to bring the -300 up to 0. The next thing I did was find which number would bring 200 up to 600 and 100 up to 300, as 600 - 300 = 300. Well, 3 * 200 = 600, but this is division so I divided 1 by 3 to get 0.3 recurring. Now, 0.3 recurring has to be formed by subtracting something from 1. The answer to 1-0.3 recurring is 0.6 recurring, so x = 0.6 recurring.
2006-12-07 14:20:02
·
answer #5
·
answered by JC 4
·
0⤊
0⤋
0 = - 300 + 200/1 - x - 100/ 1 - x
0 + 300 = - 300 + 200/1 - x - 100/1 - x + 300
300 = 200/1 - x - 100/1 - x
300 = 100/1 - x
300(1 - x) = (1 - x)(100/1 - x)
300 - 300x = 100
300 - 300x - 300 = 100 - 300
- 300x = - 200
- 300x/-300 = - 200/- 300
x = 2/3
The answer is x = 2/3
- - - - - -s-
2006-12-07 15:09:37
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
1.) add 100/(1-x) to both sides to get 100/(1-x) = -300 +200/(1-x)
2.) Multiply both sides by (1-x) to get 100 = -300*(1-x) + 200
3.) subtract 200 from both sides to get -100 = -300*(1-x)
4.) Divide both sides by -300 to get 1/3 = (1-x)
5.) Multiply by (-1) each side to get (-1/3) = x-1
6.) Add 1 to both sides to get 1-1/3 = x
7.) x = 2/3
2006-12-07 13:59:00
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
0 = 100/(1-x) - 300
300 = 100/(1 - x)
300(1 - x) = 300 - 300x = 100
200 = 300x
x = 2/3
2006-12-07 13:56:19
·
answer #8
·
answered by feanor 7
·
0⤊
0⤋